Literasi Pengelolaan Uang Saku Pada Siswa Sekolah Dasar Negeri 16 Kabupaten Seluma - Liviansyah, Liviansyah; Agusman, Kurniawan; Ratnawili, Ratnawili; Nengsih, Mimi Kurnia (Universitas Dehasen Bengkulu, 2025)
Sekolah Dasar Negeri 16 Seluma is a public primary school located in Seluma Sub-district, Seluma Regency, Bengkulu. The purpose of this socialisation is to measure the level of pocket money management literacy of students of SD 16 Seluma and identify the factors that influence it. Based on data analysis, it was concluded that the majority of students who participated in the socialisation had a poor understanding of money management literacy. The factors of financial education knowledge, saving habits, and family factors were found to have a significant relationship. Therefore, by referring to the above research, it can be concluded that there is a need to develop financial education programmes in school subjects to prepare students to become financially intelligent individuals. The method used was Forum Group Discussion (FGD) involving students of SD 16 Seluma, in this activity, namely material explanation, questions and answers and quizzes. The results of discussions and discussions in the socialisation are that to facilitate the fulfilment of needs in the future, it is necessary to have a savings and must get used to living frugally.